Developmental Trajectories of Delinquent Peer Association Among Korean Adolescents: A Latent Class Growth Analysis Approach to Assessing Peer Selection and Socialization Effects on Online and Offline Crimes - Cho, Sujung (Journal of contemporary criminal justice, 2021)
The relationship between peers and delinquency has been taken as evidence for selection and socialization effects in the etiology of adolescents. Accumulating evidence suggests that both effects are involved. This study examines whether adolescents’ aggressive propensities and behaviors predict their peers (selection) and whether peers’ propensities and behaviors predict adolescents’ behaviors (socialization). The latent class growth analysis approach revealed three distinct subgroups: an early-onset group (0.9%); a late-peak group (3.37%); and a normative group (95.73%). Both selection and socialization effects were supported using a longitudinal Korean adolescent self-report. The results showed that adolescents with less self-control who are online more frequently and exhibit higher levels of traditional bullying and delinquency were more likely to be members of both the early-onset and late-peak groups compared with the normative group. Also, the aggressive behaviors fully mediated the link between aggressive propensities and delinquent peer associations. Furthermore, adolescents in the late-peak group (but not those in the early-onset group) were associated with a greater likelihood of online and offline delinquency, but cyberbullying and traditional bullying in late adolescence levels were high in both groups’ members.